Constituencies for reform in Ghana - Bratton, M.; Lewis, P.; Gyimah-Boadi, E. (Journal of Modern African Studies, 2001)
The attitudes of ordinary people in Africa towards the liberalisation of politics and economies are not well known. Are there popular constituencies for reform? Which specific reform measures do different social groups accept or reject? And does popular support for structural adjustment, if any, go together with support for democracy? In an effort to find answers, this article reports results of a national sample survey in Ghana conducted in July 1999 as part of the Afrobarometer. The survey finds that the constituency for democracy is broader than the constituency for market reform, which is concentrated among educated male elites. In addition, while most Ghanaians are patient with democracy and want to retain this political regime, most Ghanaians are fatigued with adjustment and want the government to 'change its policies now'. Given this distribution of popular preferences, one can surmise that democracy will be easier to consolidate than a market-based economy.
Keywords: Economic reform; Constituents; Government corruption; Women; Government reform; Political attitudes; Men; Education